Applications of Coulomb crystals in cold chemistry - Gingell, A; Alexander David Gingell (2010)
This thesis describes the study of a range of ion-molecule reactions at very low collision energies using a newly developed experimental technique which involves the reaction of velocity-selected beams of translationally cold neutral molecules with very low kinetic energy ion ensembles. These studies have been enabled by the construction of a new apparatus for trapping and laser-cooling gas phase atomic ions (40Ca⁺). The laser-cooling process results in the formation of ordered, low kinetic energy, lattice-like ion structures, also known as "Coulomb crystals". The properties of single and multicomponent Coulomb crystals (which may also involve molecular ions), and their manipulation via modulation of the applied fields, are explored experimentally and with the use of molecular dynamics simulations. Variations in the laser-cooling parameters are shown to result in different steady-state populations of the electronic states of 40Ca⁺ involved with the laser cooling cycle, and these are modelled within an appropriate theoretical framework. The imaging of 40Ca⁺ fluorescence as a function of time allows the study of various ion-molecule reactions at collision energies around 300 K, with single ion sensitivity. These reaction studies are extended to low-temperature (collision energies close to 1 K), by combination of the ion trap apparatus with a bent quadrupole guide velocity-selector. Ion-molecule collision energies are shown to be variable over a short range through a change in the quadrupole guide voltage, or the ion trapping parameters; the effect of these modulations on the rate constant is explored for Ca⁺ + CH₃F. Bimolecular rate constants for the reactions of 40Ca⁺ with CH₃F, CH₂F₂ and CH₃Cl have been determined for a range of 40Ca⁺ state populations, allowing resolution of the global rate contributions from the ground and combined excited states. These results are analysed in the context of capture theories and ab initio electronic structure calculations. In each case, suppression of the ground state rate constant is explained by the presence of either a submerged or real barrier on the ground state potential surface. Rates of reaction from the combined excited states are generally found to be in line with capture theories, and in some cases variation is found between the high and low collision energy regimes. Molecular product ions generated in these experiments have been shown to be sympathetically-cooled into the crystal structure, and subsequently identified through resonance-excitation mass spectrometry. Molecular ions were also produced by multiphoton laser ionisation of a thermal background gas of OCS molecules. An ion-molecule reaction involving a molecular ion, that of charge transfer between OCS⁺ and ND₃, has been studied at a collision energy near 1 K for the first time using sympathetically-cooled OCS⁺ and velocity-selected ND₃. These experiments illustrate the generality of the techniques described herein, and should lead to many possibilities for future studies.